PENGARUH METODE PROBLEM SOLVING PADA PEMBELAJARAN DARING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Saryantono, Buang (Lentera: Jurnal Ilmiah Kependidikan, 2021)
Mathematical problem solving ability is an important ability for students to have after learning mathematics, which is also one of the learning objectives. Learning in the Covid-19 pandemic situation also requires creativity for learning actors in equipping students with these abilities. This condition is the basis for research with the aim of analyzing the effect of the Problem Solving method on online learning on the mathematical problem solving abilities of eighth grade students of SMPIT Daarul 'Ilmi Bandar Lampung, with problems in the form of low mathematical problem solving abilities. This research method is a quasi-experimental method. Hypothesis testing using parametric statistics (t-test). The research was carried out in the odd semester of the 2021/2022 academic year with a population of all eighth grade students of SMPIT Daarul 'Ilmi Bandar Lampung. The sample was taken from 2 classes, namely class VIII F as the experimental class, totaling 28, and class VIII H as the control class, totaling 28. The sample was taken using the Cluster Random Sampling technique. Students' mathematical problem solving ability is measured by a test in the form of a description of 5 questions that have been tested for validity and reliability. The results of hypothesis testing show it can be concluded that there is an effect of the Problem Solving method on online learning on students' mathematical problem solving abilities. class VIII SMPIT Daarul 'Ilmi Bandar Lampung.